THE ROLE OF INNOVATIVE TECHNOLOGIES IN THE DEVELOPMENT OF THE MODERN EDUCATION SYSTEM - Tursunboev, Otabek (Mental Enlightenment Scientific-Methodological Journal, 2024)
This article discusses the educational system of innovative technologies. Discussions on mastering education with innovative technologies will be conducted. Technologies are mentioned not only in education, but also in the field of medicine. People's connection and satisfaction with technology. About the teaching process with modern technologies in the educational institutions of our country. Lessons should be non-standard. The students' adaptation of lessons with modern technologies has given significant benefits. Working with electronic boards, computers, preparing projects is now easier. The harm of modern technology. People being made lazy by technology.